Perceived risk of cervical cancer among low-income women - Asiedu, Gladys B. (J Low Genit Tract Dis, 2014)
BACKGROUND: Risk perception is an important predictor of cancer prevention behaviors. We examined perceived risk of cervical cancer among an ethnically diverse population of women of lower socioeconomic status. MATERIALS AND METHODS: Females attending a women's health clinic were recruited for a study addressing cervical cancer prevention. Survey questions evaluated lifetime perceived risk of cervical cancer (0% to 100%), beliefs about the accuracy of the Pap test, and estimated incidence of abnormal Pap test results. Risk estimates for oneself were followed with an item seeking a brief, qualitative explanation of the risk estimate. RESULTS: Surveys were completed by 338 women. The mean (M ±SD) age of respondents was 29.9 ±8.6 years. Women self-identified as Hispanic/Latina (32%, n=107), White (34%, n=116), and African American (34%, n=115). Estimated perceived lifetime risk of getting cervical cancer ranged from 0% to 100% (M=59.2 ±29.5). Risk estimates were associated with perceived prevalence of abnormal results, r=0.24, p<0.001, and perceptions regarding the accuracy of the Pap test, r=0.13, p<0.05. On average, women estimated that nearly half of all women have ever had an abnormal result (49.2 ± 26.9; n=335; range 0%-100%), with African-American women estimating a higher percentage compared to Hispanic/Latina and White women. Women who themselves experienced an abnormal Pap test result reported higher proportions of other women experiencing an abnormal result, t(333) = −3.67, p<0.01. CONCLUSIONS: This study advances our understanding of misperception of risk and how women qualitatively view their risk of cervical cancer. The findings underscore areas for practitioners to enhance patient education efforts.